Effect of probiotic Lactobacillus paracasei on hematology and relative weight of lymphoid organs of broiler. Issue 1 (April 2020) - Hidayat, M N; Malaka, R; Agustina, L; Pakiding, W
Abstract: One alternative approach can be done to replace the antibiotic growth promotant function (AGP) in broiler, which is the use of probiotic microorganisms. The aim of this study was to look at the effects of probiotics on Lactobacillus paracasei on hematological conditions and lymphoid organs. This study used a completely randomized design consisting of 4 treatments with 5 replications, each replication using 4 broiler chickens. Treatment consists of controls (0 mL/day), probiotics 1 mL/day, probiotics 3 mL/day, and probiotics 5 mL/day. The probiotics used in this study, namely Lactobacillus paracasei (5.8 x 107 CFU/mL) were given through drinking water. The results showed that the treatment had no significant effect (p>0.05) on the number of erythrocytes, hematocrit percentage, hemoglobin level, number of leucocytes, and erythrocyte index. Likewise, treatment had no significant effect (p>0.05) on the relative weights of bursa fabricius, thymus, and spleen exchanges. The values shown in hematology parameters are all within the normal range. Whereas in the lymphoid organ parameters there is a tendency for the relative weight of lymphoid organs to be greater in the treatment of Lactobacillus paracasei than in controls. Probiotics Lactobacillus paracasei used in this study did not respond poorly to hematological features and can be used as an immunomodulator in broilers.